The Allied Japanese conspiracy - MacKay, James 1929- (Pentland Press, 1995)
"The Allied Japanese Conspiracy is the story of Asia's Forgotten Army - the Allied victims of Japanese war crimes whose experiences have been largely overlooked by the international community in the years since the end of World War II. It contains hitherto unreleased material on the extent of Japanese atrocities and James MacKay gives us the clearest articulation yet of the veteran's anger and the truth behind Japan's refusal to acknowledge its alleged crimes." "A historical overview, filling in the background to Imperial Japan's expansionist philosophy and the rise to power of General Hideki Tojo, leads in to the events that followed the entry of Japan into the war. These - the capture of Singapore and the invasion of Borneo, the Phillipines and most of the Dutch East Indies - are recounted in full and serve as a back-drop to the extensive and harrowing chapters that follow." "The eye-witness reports of the infamous Kempei Tai throwing two hundred Allied Resistance fighters to the sharks in East Java and the accounts of cannibalism and ceremonial beheadings of allied airmen stand as reason enough for the anger and indignation of Far East Veterans." "The construction of the Sumatran Railway, the part played by Emperor Hirohito in Japan's eventual surrender and The Red Army's brief but effective campaign against Japan are recalled in detail, before MacKay examines the reasons why, he believes, the Forgotten People and their families have been the victims of a conspiracy between the former Allied powers and the Japanese government, designed to keep the communists out of South East Asia."--BOOK JACKET.